2018
DOI: 10.1002/ppsc.201700448
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugated Core–Shell Microparticles for High‐Force Optical Trapping

Abstract: Due to their high spatial resolution and precise application of force, optical traps are widely used to study the mechanics of biomolecules and biopolymers at the single‐molecule level. Recently, core–shell particles with optical properties that enhance their trapping ability represent promising candidates for high‐force experiments. To fully harness their properties, methods for functionalizing these particles with biocompatible handles are required. Here, a straightforward synthesis is provided for producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Recently, bio-conjugated core-shell micro-particles were found to have better trap stiffness compared with conventional (core-type) plastic microspheres and were utilized in high force experiments to probe the mechanics of stable protein structures [25]. Using different beam profiles, it was also reported that different types of core-shell particles can enhance the trapping efficiency of core-shell particles in comparison to conventional (core-type) particles [26,27].…”
Section: Hollow-core Type Particlesmentioning
confidence: 99%
“…Recently, bio-conjugated core-shell micro-particles were found to have better trap stiffness compared with conventional (core-type) plastic microspheres and were utilized in high force experiments to probe the mechanics of stable protein structures [25]. Using different beam profiles, it was also reported that different types of core-shell particles can enhance the trapping efficiency of core-shell particles in comparison to conventional (core-type) particles [26,27].…”
Section: Hollow-core Type Particlesmentioning
confidence: 99%
“…[19][20][21] These metal-dielectric core-shell particles have other advantages such as improved chemical and physical properties, catalytic properties, improved biocompatibility, etc., which makes them good candidates for bio-conjugated experiments. [22][23][24] A number of techniques and procedures emerged for fabrication of these particles with a controllable composition and morphology, [25][26][27] opening up the possibilities of using these particles in the aforementioned wide range of applications. [15][16][17][18][22][23][24] In this article, we discuss how optical trapping efficiency changes with the nature of metal/dielectric core/shell particles, which consist of an inner core made of metal and an outer shell or covering made of dielectric or vice versa as well as hollow-core type nanoparticles as well.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] A number of techniques and procedures emerged for fabrication of these particles with a controllable composition and morphology, [25][26][27] opening up the possibilities of using these particles in the aforementioned wide range of applications. [15][16][17][18][22][23][24] In this article, we discuss how optical trapping efficiency changes with the nature of metal/dielectric core/shell particles, which consist of an inner core made of metal and an outer shell or covering made of dielectric or vice versa as well as hollow-core type nanoparticles as well. Specically, using the dipole approximation, we show theoretical/numerical results on the role of optical nonlinearity in modulating trapping behavior when femtosecond pulsed excitation is used.…”
Section: Introductionmentioning
confidence: 99%
“…By wielding advanced materials with optical tweezers, , a new toolkit arises for interrogating chemistry at the limits of space and time. In doing so, the microscope is transformed into a nN tensiometer, a scanning probe with spatial and spectroscopic resolution, a photonic soldering iron, or a local heat source. , It would be desirable to apply any combination of these tools with broad solvent compatibility. For single-molecule studies of polymers, dual trap optical tweezers allow for a single-molecule tether to be constructed between two microspheres (typically polystyrene or silica “beads”).…”
Section: Introductionmentioning
confidence: 99%